THE PERPENDICULAR DIPOLE METHOD AT NEAR-SURFACE RESISTIVITY SOUNDING, A CASE STUDY OF ANDESITE DEPOSIT - D KUSUMO (NIM : 22107025), ADRIYANTO
The electrical resistivity method is one of geophysical method which has been used for natural resources applications, such as : hydrogeology, mining, and geotechnical. In literature, the dipole-dipole variations of electrical sounding methods (1D) have been used for rock formation detection in deep exploration and anomalies detection in geothermal exploration. The research of perpendicular dipole variations have not been studied to identify rock in near-surface. The electrical sounding measurements were conducted in various values of θ (dipole angle), L (dipole length), and r (dipole separation). The θ values were conducted in various angles of 100, 300, 450, dan 600. The L values were conducted in 5 and 10 metres length. The r values were conducted in various distance of 5, 10, 15, 20, 25, 30, 40, and 50 metres. These various values were conducted in order to know the influence of apparent resistivity curves and the distribution of apparent resistivity values. The result of electrical resistivity sounding with perpendicular dipole showed that the apparent resistivity curve variations occured in L value less than 30 metre. At spacing L greater than 30 metres, the curve became nearly independent of L spacings. The ambiguity of interpretation could occur if the apparent resistivity curve was different. These condition could be minimized by detecting geological condition of study area. The forward modeling result showed that the apparent resistivity curve variations occured at spacing L less than 15 metres. At spacing L greater than 15 metres, the curve became nearly independent of L spacings. The dipole angle deviation, from 10 to 50 with L value greater than 15 metres, showed the same layer interpretation which means there is no interpretation ambiguity.